1978
DOI: 10.1159/000122818
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Adenohypophyseal Hormone Changes Induced by Various Stressors in Female and Male Rats

Abstract: Plasma modifications of adenohypophyseal hormones were investigated in groups of female and male rats stressed for 15, 30 min, 1, 2, 4 or 6 h, either by cold (4°C), forced muscular exercise (FME), or immobilization. GH levels in both female and male rats were consistently decreased by the 3 stressing agents. Immobilization in the female and the 3 stressors in the male elicited an early secretory response of prolactin (Prl), while only in immobilized female rats plasma LH levels showed an early, short-lived inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…Other studies reported both in creases [3,30] and decreases [31,32] in PRL after cold exposure, and these different findings may represent nonspecific effects since PRL respond rapidly to stress [31][32][33]. With regard to the cold-associated stimulation of the thyroid function, this response seems specific for the cold stress since other types of stress are known to reduce, rather than to increase, TSH levels [33].…”
Section: Discussionmentioning
confidence: 93%
“…Other studies reported both in creases [3,30] and decreases [31,32] in PRL after cold exposure, and these different findings may represent nonspecific effects since PRL respond rapidly to stress [31][32][33]. With regard to the cold-associated stimulation of the thyroid function, this response seems specific for the cold stress since other types of stress are known to reduce, rather than to increase, TSH levels [33].…”
Section: Discussionmentioning
confidence: 93%
“…TSH was also evaluated under basal and stress conditions in adult males, as immobilization stress has been reported to reduce the TSH levels in rodents [25, 26]. Both genotypes responded to immobilization stress with a similar decrease in TSH levels (fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that a suckling-induced TSH increase is abolished by baclofen administration in the rat [6], suggesting a participation of GABA B Rs in TSH regulation. In addition, stress was shown to influence the TSH secretion, increasing or decreasing its levels, depending on the stressor used [25, 26]. We, therefore, evaluated basal TSH levels and their response to immobilization stress in null mutant and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…In sub-mammalian species also, n petitive presentation of the same stressor over a long perio resulted in gradual diminution of the plasma corticoid ris e.g., Salmo irrideus, Rana esculenta. Anas platyrhynchos [13 However, other workers did not find any change in th magnitude of the corticosteroid response during repeated exposure to a stressor in mammals [9,12,27] or in birds |-11], In this respect, it is interesting to note that in rats adapted to traumatization in a Noble-Collip drum, the magnitude of the adrenocortical reaction immediately after injury was as high as in non-adapted controls. However, their increased plasma corticosterone level returned more rapidly to the basal value after injury [15].…”
Section: Discussionmentioning
confidence: 96%